Kunci Sukses Kinerja Karyawan: Dampak Tingkat Pendidikan dan Pengalaman Kerja pada PT. Bangunpapan Idaman - Erika Nursinta Sari; Nuraeni Nuraeni (Dinasti Research, 2025)
This study aims to determine and analyse the effect of education level and work experience on employee performance in PT.Bangunpapan Idaman. The data obtained from the employees of PT.Bangunpapan Idaman are secondary data and primary data. The population used in this study was 70 employees. The sampling technique uses a method or saturated sampling technique where all populations are sampled. The method used is multiple linear regression analysis method using SPSS software. The results of the t-test calculation, the level of education has a positive and significant effect on employee performance because the tcount value is greater than the ttable with a value of 5.037> 1.996. Then it is known that the sig value is 0.000 where the sig value is less than 0.05 or 0.000 <0.05, so Ho is rejected and Ha is accepted, which means that the level of education has a positive and significant effect on employee performance. Work experience has a positive and significant effect on employee performance because the tcount value is greater than the ttable with a value of 4.433> 1.996. Then it is known that the sig value is 0.000 where the sig value is less than 0.05 or 0.000 <0.05, so Ho is rejected and Ha is accepted, which means that work experience has a positive and significant effect on employee performance.